Improved phase change behavior of Sb2Se material by Si addition for phase change memory. (1st April 2016) - Hu, Yifeng; Zou, Hua; Yuan, Li; Xue, Jianzhong; Sui, Yongxing; Wu, Weihua; Zhang, Jianhao; Zhu, Xiaoqin; Song, Sannian; Song, Zhitang
Abstract: Compared with Sb2 Se, Si–Sb–Se material is proved to be a promising candidate for phase change memory (PCM) use because of its higher crystallization temperature (~ 230 °C), larger crystallization activation energy (3.25 eV), and better data retention ability (168 °C for 10 years). Furthermore, the fast crystallization time 3.30 ns is obtained for Si0.20 (Sb2 Se)0.80 material by the picosecond laser technique. The set switching is realized with low threshold current 6.9 μA and voltage 1.80 V, respectively. The reverse resistance transition can be achieved by an electric pulse as short as 8 ns for Si0.20 (Sb2 Se)0.80 -based PCM cell. Graphical abstract: Compared with Sb2 Se, Si–Sb–Se material possesses higher crystallization temperature, indicating better thermal stability. The growth dominated crystalline mechanism makes Si–Sb–Se-based phase change memory device can have fast SET/RESET speed (8 ns). Si–Sb–Se material is proved to be a promising candidate for phase change memory with good thermal stability and high phase change speed.